2016
DOI: 10.1093/molbev/msw163
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Evolution of a Large Multidrug Resistance Plasmid in New Clinical Bacterial Hosts

Abstract: Large conjugative plasmids are important drivers of bacterial evolution and contribute significantly to the dissemination of antibiotic resistance. Although plasmid borne multidrug resistance is recognized as one of the main challenges in modern medicine, the adaptive forces shaping the evolution of these plasmids within pathogenic hosts are poorly understood. Here we study plasmid–host adaptations following transfer of a 73 kb conjugative multidrug resistance plasmid to naïve clinical isolates of Klebsiella p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
268
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 218 publications
(285 citation statements)
references
References 62 publications
12
268
5
Order By: Relevance
“…Several reports pinpoint conjugation as a source of plasmid cost for the bacterial host (28,64,65). For example, the fitness cost associated with plasmids R1 and RP4 in E. coli is reduced after the conjugation rate is decreased or abolished by natural selection in an experimental setting (64).…”
Section: Conjugationmentioning
confidence: 99%
See 4 more Smart Citations
“…Several reports pinpoint conjugation as a source of plasmid cost for the bacterial host (28,64,65). For example, the fitness cost associated with plasmids R1 and RP4 in E. coli is reduced after the conjugation rate is decreased or abolished by natural selection in an experimental setting (64).…”
Section: Conjugationmentioning
confidence: 99%
“…Also, the expression of plasmid R1 conjugation genes has been shown to activate stress responses in E. coli (65), although it is not clear if this is cause or consequence of the cost of plasmid carriage. Finally, in a recent analysis of the IncN antibiotic resistance plasmid pKP33, Porse and colleagues showed that the loss of the conjugation region reduced the burden associated with plasmid carriage in E. coli (28).…”
Section: Conjugationmentioning
confidence: 99%
See 3 more Smart Citations